Development of a cross-linked quaternized poly(styrene-b-isobutylene-b-styrene)/graphene oxide composite anion exchange membrane for direct alkaline methanol fuel cell application. Issue 57 (27th May 2016) - Dai, Pei; Mo, Zhao-Hua; Xu, Ri-Wei; Zhang, Shu; Lin, Xiao; Lin, Wen-Feng; Wu, Yi-Xian
Abstract : A crosslinked quaternized poly(styrene- b -isobutylene- b -styrene)/graphene oxide composite anion exchange membrane showed high ionic conductivity and low methanol permeability. Abstract : A cross-linked quaternized poly(styrene- b -isobutylene- b -styrene)/graphene oxide composite anion exchange membrane has been prepared via intercalation of organo-modified graphene oxide (GOA), and characterized as a promising anion exchange membrane for direct alkaline methanol fuel cell application. In order to further increase the ionic conductivity of the composite membrane, quaternized GOA (GOAN) was introduced into QSIBS. Compared with the Nafion® membrane, the new anion exchange membranes show a comparable ionic conductivity (1.95 × 10 −2 S cm −1 ) but much lower methanol permeability (1.7 × 10 −7 cm 2 s −1 ). The QSIBS/0047OAN-0.50 wt% composite membrane has the highest selectivity, which is about 12 times higher than that of the Nafion 115 membrane. The promising performance is attributed to two factors: one is the barrier effect of the quaternized octadecylamine-functionalized graphene oxide sheets, which is unfavourable for methanol crossover; and the other is the presence of interconnected ionic transportation channels between the incorporated modified graphene oxide and polymer, which is favourable for ionic transport.